The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1159/000511111
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of a Patient with Brentuximab Vedotin-Refractory ALK-Negative Anaplastic Large Cell Lymphoma with Romidepsin

Abstract: We present the case of a 78-year-old male patient who was diagnosed with anaplastic lymphoma kinase (ALK)-negative, CC chemokine receptor 4 (CCR4)-negative, and CD30-positive anaplastic large cell lymphoma (ALCL). The patient had a past medical history of adult T-cell leukemia/lymphoma and colon cancers that had developed simultaneously approximately 2 years prior to the development of ALCL that were treated with immunochemotherapy and resection, respectively. Initial treatment for ALCL included brentuximab ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Fortunately, the patient achieved CR for ALCL through treatment with romidepsin. The Tax‐specific CTLs were maintained at high percentages during the romidepsin therapy and until the last follow‐up without any relapse of ATLL and ALCL in this patient 41 . These results suggest that mogamulizumab alone is insufficient to induce adequate Tax‐specific CTLs production.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Fortunately, the patient achieved CR for ALCL through treatment with romidepsin. The Tax‐specific CTLs were maintained at high percentages during the romidepsin therapy and until the last follow‐up without any relapse of ATLL and ALCL in this patient 41 . These results suggest that mogamulizumab alone is insufficient to induce adequate Tax‐specific CTLs production.…”
Section: Discussionmentioning
confidence: 68%
“…The Tax‐specific CTLs were maintained at high percentages during the romidepsin therapy and until the last follow‐up without any relapse of ATLL and ALCL in this patient. 41 These results suggest that mogamulizumab alone is insufficient to induce adequate Tax‐specific CTLs production. Herpes virus infection has been reported to activate innate and adaptive immune responses, which include the release of inflammatory cytokines and chemokines.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Romidepsin-mediated tumor suppression was abrogated by anti-PD-1 antibody treatment in colon cancer cells ( 61 ). One case report showed that romidepsin might be safe and effective for treatment of anaplastic large cell lymphoma (ALCL), which did not impair cellular immunity to HTLV-1 ( 62 ).…”
Section: Role Of Hdac In Immunotherapymentioning
confidence: 99%